Effects of tahitian noni juice on ketamine anaesthesia in some local rabbits (2010)
Tahitian Noni Juices (TNJ) from Morinda citrifolia is known with some therapeutic properties that include; anxiety and stress relief, production of calm and relax state, improvement of mood and sense of well being, and sleep restoration. This study attempt to evaluate TNJ effects in some ketamine sedated local rabbits. Six adult rabbits (1.5-1.7 kg) were given intramuscular injection of 5% ketamine hydrochloride (40 mg/kg), following which the quality of sedation w as evaluated using: muscle relaxation/rigidity, presence or loss of pain sensation, quality of amnesia as well as heart rate, respiratory rate and temperature as control values. TNJ was administered orally at 2 mL/kg twice daily for 28 days during which period ketamine injection was repeated at 7 days interval. Presence of muscle relaxation or rigidity, presence or absence of pain sensation, quality of amnesia as well as heart rate, respiratory rate and temperature were evaluated. Duration of sleep before and after noni administration was 40.7±9.6 and 46.8±13.7 min, respectively. There was improved quality of amnesia and behavioral responses. Rough induction and recovery gave way to smooth induction and recovery, and spontaneous movement during anesthesia was minimized. Salivation w as abolished in all except one rabbit. Mean basal heart rate before and after administration of noni were 204.8±48.4 and 264.4±35.6 beats per min, respectively. Basal respiratory rate also increased from 192±46.3 to 317.6±66.4 breaths per min. TNJ produced appreciable level of calmness, muscle relaxation, and loss of anxiety, and could be useful for premedication prior to aneasthesia